Analisis Aspek Fungsional Kesiapsiagaan Bencana di Rumah Sakit Umum Rajawali Citra 2021 - Hodiri Adi Putra (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2021)
ABSTRACT                                                                   Background of Study : Hospital preparedness for disasters is reflected in the structure of the disaster team. Measurement of preparedness is needed for the identification and classification of disaster management. This study aims to analyze the functional aspects of disaster preparedness at the Rajawali Citra General Hospital. Methods : The research is a qualitative descriptive using purposive sampling method. The sample is an employee who has a position in hospital disaster management. The validity of the data used triangulation of sources and methods while the data analysis used content analysis after being processed with open code. The measurement instrument used the 2015 Hospital Safety Index criteria. Results : The results showed that the hospital disaster management team had officially been formed by the Rajawali Citra General Hospital to respond to disaster situations. As a disaster preparedness hospital, it is reflected in the structure of the disaster management team that has been mutually agreed upon. The hospital disaster team has carried out disaster training to improve knowledge and skills, the hospital's Emergency Operations Center is in a safe and easily accessible and protected area, equipped with an evacuation route map, the hospital has collaborated with external disaster management teams such as the local government. fire and local disaster management agencies. Action cards for all personnel already exist, including disaster vest uniforms.Conclusion : Based on the results of the study, it can be concluded that the hospital has implemented functional aspects of disaster preparedness, this can be seen from the existence of a disaster committee, having disaster training, having an emergency operations center, collaborating with regional disaster management agencies and having a disaster identity card. Keywords : Functional Aspects, Preparedness, Disaster